2013
DOI: 10.1002/eqe.2368
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating intensity bounds for assessing the seismic safety of structures: Does it matter?

Abstract: SUMMARY The closed‐form solution for assessing the proportion of the mean annual frequency of limit‐state exceedance as a function of integration limits is introduced, in order to study whether or not the mean annual frequency of limit‐state exceedance is overestimated if the lower and(or) upper integration limit of the risk equation are(is) not selected in a physically consistent manner. Simple formulas for assessing the threshold value of the lower and upper integration limits are also derived. These formula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

7
0

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 42 publications
(108 reference statements)
0
53
1
Order By: Relevance
“…However, the correction factor C 1 has a different meaning than the proportion of the limit-state risk Dk LS,im1 , which was defined and presented in Fig. 4 of the previous study [11]. By comparing these two parameters it can be concluded that the effect of the lower bound of intensity is slightly reduced in the case of the correction factor C 1 since this factor is based on the truncated limit-state fragility function (Eq.…”
Section: Theoretical Background and Derivationsmentioning
confidence: 93%
See 3 more Smart Citations
“…However, the correction factor C 1 has a different meaning than the proportion of the limit-state risk Dk LS,im1 , which was defined and presented in Fig. 4 of the previous study [11]. By comparing these two parameters it can be concluded that the effect of the lower bound of intensity is slightly reduced in the case of the correction factor C 1 since this factor is based on the truncated limit-state fragility function (Eq.…”
Section: Theoretical Background and Derivationsmentioning
confidence: 93%
“…This assumption is the main difference between the formulae introduced in this paper and those published before [11]. The truncated fragility function is therefore expressed as follows:…”
Section: Theoretical Background and Derivationsmentioning
confidence: 97%
See 2 more Smart Citations
“…Commonly lognormal distribution of collapse fragility function is used. Lazar and Dolšek [15] showed that standard deviation of natural logarithms of collapse intensities in terms of spectral acceleration at fundamental period in the case of reinforced concrete frames is within the interval from 0.3 to 0.5. To minimize the influence of error in assumed standard deviation of natural logarithms of collapse intensities β t on the value of S a,ct Dolšek and Brozovič [13] showed that the target collapse intensity should be associated with a low percentile, so-called characteristic percentile, of collapse intensities.…”
Section: Assumptionsmentioning
confidence: 99%